Vestibular suppression of normal bodily sounds. (3rd May 2020) - Longridge, Neil S.; Lim, Anielle; Mallinson, Arthur Ian; Renshaw, Jim
Abstract: Background: Vestibular-evoked myogenic potentials (VEMPs) are present in almost everyone. The proximity of the cochlear and vestibular end organs strongly indicates an overlap of the stimuli to which they respond. Aims/objectives: To determine the loudness of shouting compared to the external auditory canal (EAC) and explore how hyperstimulation of the cochlea and vestibular structures might be prevented. Materials and methods: We compared the loudness and frequency response of sound during shouting, biting and chewing, as well as the measurement of the loudness and frequency of sound in the external auditory canal (EAC) when a calibrated minishaker is applied to the forehead and to the upper incisor teeth. Results: We showed that vibratory sounds produced by vocalizations and oral activities were attenuated when they reached the ear, so that these sounds would not act as vestibular stimulants. Conclusions and significance: Chewing is known to cause a stapedius reflex which suppresses internal sounds to optimize audition of external sounds, while at the same time suppressing vestibular stimulation, which serves to optimize the sensitivity of the vestibular system, in order that it may respond precisely to a threat.